The relationship of cervicothoracic mobility restrictions to fall risk and fear of falling in ankylosing spondylitis - Johnston, Janine L.; Harms, Shane L.; Thomson, Glen T. D. (Frontiers in Medicine, 2023)
Objective The objective of this study is to determine whether restricted cervical mobility in ankylosing spondylitis (AS) is associated with increased fall frequency or fear of falling. Methods A total of 134 AS patients and 199 age- and gender-matched control subjects (CS) with soft-tissue cervicothoracic pain were prospectively evaluated for fall risk. Subjects were divided into non-fallers, single fallers, and multiple fallers. Dynamic cervical rotations and static cervicothoracic axial measurements were compared between the groups. In total, 88 AS patients were reviewed more than once; Kaplan–Meier plots were constructed for fall risk as a function of cervical rotation amplitudes. Falls Efficacy Scale-International (FES-I) questionnaire measured the fear of falling. Results In total, 34% of AS patients and 29% of CS fell (p = 0.271) in the year prior to evaluation. In AS, static anatomical measurements were unrelated to fall occurrence. The trends of multiple AS fallers to greater flexed forward postures and reduced dynamic cervical rotations were not statistically significant. Cervicothoracic pain (p = 0.0459), BASDAI (p = 0.002), and BASFI (p = 0.003) scores were greater in multiple fallers. FES-I scores were greater in fallers (p = 0.004). Of the 88 AS patients reviewed (or seen) on more than one occasion, 46.5% fell over the 9-year observation period, including all multiple fallers and 71.4% of single fallers. Survival curves showed increased fall risk as cervical rotational amplitudes decreased. Conclusion In AS, decreased cervical rotations increase fall risk and fear of falling. In multiple fallers, falls were associated with greater disease activity. Cervical muscle stiffness in AS may cause non-veridical proprioceptive inputs and contribute to increased fall frequency similar to individuals with soft-tissue cervicothoracic pain.